A comparison among two composite models (without regression processing) and (with regression processing), applied on Malaysian imports - Milad M.A.H.; Ibrahim R.I.; Marappan S. (Hikari Ltd., 2024)
Applied Mathematical Sciences, Vol. 9, 2015, no. 116, 5757 - 5767Indexed by Scopus